Stabilization and functional properties of Escherichia coli penicillin G acylase by covalent conjugation of anionic polysaccharide carboxymethylcellulose - (:unkn) unknown (SPRINGER, 2002)
The stabilization of Escherichia coli penicillin G acylase ( PGA) conjugated with carboxymethylcellulose (CMC) against temperature and pH was studied. The 2,3-dialdehyde derivative of CMC obtained by periodate oxidation was covalently conjugated to PGA via Schiff's base formation. The inactivation mechanism of both native and CMC-conjugated PGA appeared to obey first order inactivation kinetics during prolonged incubations at 40-60degreesC and in the pH range 4-9. Inactivation rate constants of conjugated enzyme were always lower, and half-life times were always higher than that of native PGA. The activation free energy of inactivation (DeltaG(i) values) of CMC-conjugated enzyme were found to be always higher than that of native PGA at all temperatures and pH values studied as another indicator of enzyme stabilization. Highest stability of CMC-conjugated enzyme was observed as nearly four-fold at 40 degreesC and pH 8.0. No changes were observed on the temperature and pH profiles of PGA after CMC conjugation. Lower K-m and higher k(cat) values of PGA obtained after CMC conjugation indicates the improved effect of conjugation on the substrate affinity and catalytic performance of the enzyme.
Keywords: carboxymethylcellulose; covalent conjugation; enzyme stabilisation; Escherichia coli; inactivation kinetics; penicillin G acylase; CHEMICAL MODIFICATION; ENZYME STABILIZATION; ASPERGILLUS-NIGER; CROSS-LINKING; ALPHA-AMYLASE; THERMOSTABILIZATION; ATCC-11105; STABILITY; KINETICS; TRYPSIN